Decreasing Heart Rate After Physical Activity Reduces Choking - Hine, Kyoko; Takano, Yuto (Frontiers in Psychology, 2020)
We occasionally place our bodies under pressure, for example, by playing sports or giving an important presentation at a business meeting. In such situations, most of us have experienced choking, which impairs performance. It has been reported that controlling the heart rate is effective at reducing anxiety, which is one of the causes of choking. Previous studies have proposed a method of reducing choking by undergoing special training for controlling heart rate. Here, we investigated whether a reduction in heart rate after physical activity reduces choking without any special training. Participants bowled under both high-pressure and low-pressure conditions. Before throwing the bowling ball, half of the participants ran on the spot (active condition), whereas the rest of the participants stood instead of running (inactive condition). After controlling for the baseline score, the bowling score in the high-pressure and active condition was significantly better than that in the inactive condition. Additionally, the reduction in heart rate in the active condition was larger than that in the inactive condition. These results suggest that the reduction in heart rate prevented choking without any specific training.